Project-Based Learning Oriented E-Worksheets with QR Code Packaging: Validity and Practicality - Pranata, I Kadek Adi; Parmiti, Desak Putu; Agustiana, I Gusti Ayu Tri (Thinking Skills and Creativity Journal, 2024)
The lack of use of innovative student worksheets makes the learning process less effective because it does not facilitate the student learning process properly. This study aims to describe the design, validity and practicality of electronic student worksheets oriented towards Project Based Learning with QR Code packaging on the fourth grade elementary school science content. This study uses the ADDIE model (analysis, design, development, implementation, evaluation). Data collection methods are carried out by observation, interviews, document studies, and questionnaires. Data analysis techniques use quantitative descriptive analysis and qualitative descriptive analysis. The results of this electronic student worksheet development research are: the design of electronic student worksheets oriented towards Project Based Learning with QR Code packaging on the fourth grade elementary school science content, electronic student worksheets are declared valid and feasible based on the validity index of 0.90 and the feasibility analysis of media experts obtained a validity index of 0.88, and is included in the range ≥ 0.8 meaning that the product developed is included in high validity. Based on these results, it can be concluded that the electronic student worksheet oriented towards Project Based Learning with QR Code packaging on the fourth grade elementary school science content is valid and suitable for use in the learning process.